Stand alone photovoltaic-wind hybrid system for 100w motor - Mohd Nasir, Mohamad Na'im; Saharuddin, Nur Zawani; Yahaya, Muhammad Sharil; Jamri , Mohd Saifuzam; Ismail, Irshad (2012)
Hybrid system of Photovoltaic (PV) - Wind turbine (WT) generation has more advantages compared to PV or wind turbine system alone. The main objective of this paper is to study the characteristic of the hybrid system of PV-WT besides supplying 100W permanent-magnet dc motor with this type of sources. The aim is also to design a hybrid system of PV-WT for the source of 100W permanent-magnet dc motor. To achieve the objective, both of PV and WT are connected to converter in order to get the same source of DC supply. Then both source were combine or hybrid and straightly connected to 100W permanent magnet dc motor. All the works in this paper is only apply in circuit simulator of Matlab Simulink. The output source from each converter is expected to be suit to the motor specification. The value of the output source from each renewable energy system is as expected to be high as it can support the motor if one of them is breakdown.